2006
DOI: 10.1126/science.1124000
|View full text |Cite
|
Sign up to set email alerts
|

Histone H4-K16 Acetylation Controls Chromatin Structure and Protein Interactions

Abstract: Acetylation of histone H4 on lysine 16 (H4-K16Ac) is a prevalent and reversible posttranslational chromatin modification in eukaryotes. To characterize the structural and functional role of this mark, we used a native chemical ligation strategy to generate histone H4 that was homogeneously acetylated at K16. The incorporation of this modified histone into nucleosomal arrays inhibits the formation of compact 30-nanometer-like fibers and impedes the ability of chromatin to form cross-fiber interactions. H4-K16Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

70
1,431
7
23

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,677 publications
(1,531 citation statements)
references
References 22 publications
70
1,431
7
23
Order By: Relevance
“…46 Acetylation of H4K16 inhibits formation of the higher order 30 nm chromatin structure, and loss of H4K16 shows defects equivalent to the loss of the H4 tails. 69 The increased acetylation of H4K16 observed in Hdac2-deficient oocytes likely contributes to the failure of chromosomes to condense fully during oocyte maturation and compromised kinetochore function in mutant eggs, because reducing H4K16 acetylation by overexpressing HDAC2 in Hdac2 −/− oocytes restores normal chromosome condensation and segregation. 46 A recent report also provides further evidence that H4K16 deacetylation has an important role in maintaining normal chromatin structure in oocyte maturation; H4K16 hyperacetylation induced by knockdown of SIRT2, a member of Class III HDACs, leads to spindle defects, missegregation of chromosome and impaired kinetochore-microtubule interaction.…”
Section: Hdac2 Regulates Chromosome Segregation and Kinetochore Functmentioning
confidence: 99%
“…46 Acetylation of H4K16 inhibits formation of the higher order 30 nm chromatin structure, and loss of H4K16 shows defects equivalent to the loss of the H4 tails. 69 The increased acetylation of H4K16 observed in Hdac2-deficient oocytes likely contributes to the failure of chromosomes to condense fully during oocyte maturation and compromised kinetochore function in mutant eggs, because reducing H4K16 acetylation by overexpressing HDAC2 in Hdac2 −/− oocytes restores normal chromosome condensation and segregation. 46 A recent report also provides further evidence that H4K16 deacetylation has an important role in maintaining normal chromatin structure in oocyte maturation; H4K16 hyperacetylation induced by knockdown of SIRT2, a member of Class III HDACs, leads to spindle defects, missegregation of chromosome and impaired kinetochore-microtubule interaction.…”
Section: Hdac2 Regulates Chromosome Segregation and Kinetochore Functmentioning
confidence: 99%
“…The apo and holo nuclear receptor complexes initiate specific and coordinated histone modifications (69,70) to govern transcriptional responsiveness of the promoter. There is good evidence that specific histone modifications also determine the assembly of transcription factors on the promoter and control individual promoter transcriptional responsiveness (71)(72)(73) . It is less clear to what extent nuclear receptors recognize basal histone modifications on target gene promoters; functional studies of the SANT motif contained in the co-repressor NCoR2/SMRT support this latter idea (74) .…”
Section: Metabolism Of Cholecalciferol and Major Cholecalciferol Funcmentioning
confidence: 99%
“…Evidence for this mechanism comes from the finding that histone hyperacetylation is known to increase the accessibility of nucleosomal DNA to transcription factors and other co-activators in budding yeast (Anderson et al, 2001). Furthermore, elegant in vitro studies have shown that synthetic acetylation of H4 at K16 alone is sufficient to inhibit the formation of condensed 30 nm chromatin fibers and cross-fiber interactions (Shogren-Knaak et al, 2006). A second model is founded on the fact that certain protein motifs are able to recognize specifically chemically modified histone tails.…”
Section: H4k16ac In Chromatin Organizationmentioning
confidence: 99%